The security society as consequences of life in liquid times - Marek Jerzy Cendrowski (Lubelski Rocznik Pedagogiczny, 2019)
The article discusses the issue of attitudes and behaviors of the 21st-century man in the perspective of the threats of the modern world, resulting from the conditions of the “network society”. The importance of security, as the main human need, in the context of socio-political changes at the turn of the 20th and 21st centuries and rapidly developing information technologies, constitutes a pretext to formulate the thesis about the emergence of a specifically shaped security society. This paper is an attempt to understand the attitudes and behaviors of modern man, with particular emphasis on the conditions related to the changing social reality.